Scientific Societies Fostering Inclusivity in the Life Sciences Through Engagement of Undergraduate Scientists - Primus, Clara; Zimmerman, Alexandra N.; Terovolas, Avanthia K.; Block, Kirsten F.; Brown, Christopher G.; Burton, Michael D.; Edwards, Ashanti; Etson, Candice M.; Flores, Sonia C.; Fry, Catherine; Guillory, Ashley N.; Ingram, Susan L.; et al. (Frontiers in Education, 2022)
Scientific societies serve as communities of practice in which scientists develop many of the skills and connections required for the progression of their careers. For example, scientific societies offer a range of opportunities to attend career development programs, gain experience in communicating science, and receive recognition for achievements within their discipline. Programming for undergraduate student members has recently been increasing, both in prevalence and in its range of offerings. The Alliance to Catalyze Change for Equity in STEM Success, ACCESS, a meta-organization seeking equity and inclusivity in life sciences fields, has examined programs and opportunities focused on undergraduates across its member scientific societies to identify common themes, promising practices and challenges. In this article, we share and discuss our findings.